Sebuah Pengembangan Media Video Pembelajaran Berbasis Web Tari Lima Serangkai Suku Karo untuk Meningkatkan Pengetahuan dan Keterampilan Tari Pemuda GBKP Surabaya": Pengembangan Media Video Pembelajaran Berbasis Web Tari Lima Serangkai Suku Karo untuk Meningkatkan Pengetahuan dan Keterampilan Tari Pemuda GBKP Surabaya" - Egy Sry Ulina Br Ginting; I Nengah Mariasa (Jurnal Pendidikan Sendratasik, 2026)
This study aimed to develop a web-based learning video media for the Lima Serangkai Dance of the Karo ethnic group and to determine the feasibility and effectiveness of the developed media in improving dance knowledge and skills among youth members of the Batak Karo Protestant Church (GBKP) in Surabaya. This research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 15 youth members of GBKP Surabaya aged 20–28 years. Data were collected through observation, interviews, documentation, questionnaires, and tests, then analyzed using quantitative descriptive and N-Gain analysis. The results showed that the developed media received validation scores ranging from 83.33% to 95.76%, all categorized as Very Feasible. The effectiveness test showed that the average pretest score of 63.33 increased to 94.00 in the posttest, with an N-Gain score of 0.85 (high category). Students’ dance skills also improved from the Adequate to the Very Good category. Therefore, the developed web-based learning video media for Lima Serangkai Dance is feasible and effective in improving the knowledge and skills of GBKP Surabaya youth. Penelitian ini bertujuan mengembangkan media pembelajaran video berbasis web tari Lima Serangkai Suku Karo dan mengetahui kelayakan serta keefektifannya dalam meningkatkan pengetahuan dan keterampilan tari pemuda GBKP Surabaya. Metode R&D dengan model ADDIE digunakan dengan 15 subjek penelitian usia 20–28 tahun. Hasil validasi ahli menunjukkan skor 83,33%–95,76% (Sangat Layak). Nilai rata-rata pretest 63,33 meningkat menjadi 94,00 pada posttest dengan N-Gain 0,85 (kategori Tinggi). Keterampilan tari meningkat dari kategori Cukup menjadi Sangat Baik. Keywords: learning media, web-based video, Lima Serangkai Dance, ADDIE model, learning outcomes